Driving a three-age learning curriculum from local wisdom under the “YANGKHINOK Model” in Thailand - Pearnpitak, Kittipong; Akahat, Noppon; Moungon, Pratueng (Humanities, Arts and Social Sciences Studies, 2024)
This study had the objective of developing a three-age learning curriculum from local wisdom under the YANGKHINOK Model which focuses on time, resources, knowledge, skills, and sincerity to enhance competency and leverage social networks in Khueang Nai District, Ubon Ratchathani Province, Thailand. Due to the dynamics of global society influencing Thai education, integrating local wisdom in curriculum development is essential for preserving cultural heritage and community sustainability. A mixed method of qualitative case studies and quantitative evaluation was employed to assess the efficacy of the local wisdom project. Key findings spotlighted the importance of community participation, educational coordination, and the appropriate development of a curriculum for all age groups by the YANGKHINOK Model (Youth, Adult, Narration, Gathering, Knowledge, Hearkening, Impetus, Network, Older Persons, Keeping). This inclusive approach emphasizes the critical role of collaboration among local communities and educational institutions to ensure that the curriculum remains relevant and adaptable across different generations. The approach also aims to create a contemporary democratic society by promoting continuous learning and sustainable professional development that fosters long-term community resilience. It was concluded that a sustainable community curriculum must include these components to meet the actual needs of the community, as well as being adaptable to social and economic changes. Effective use of limited local resources, strategic planning, and broad participation for practical results lead to lasting sustainability, providing a framework for continuous community improvement.